Çoklu ürün ekosistemlerinde kullanıcı deneyimi: Akıllı banyo baskülleri üzerinden bir inceleme - Baş, Ceyda (Fen Bilimleri Enstitüsü, 2020)
Yakın geçmişte, dijital ürünler sadece bilgisayar ya da telefon üzerinden kullanılmakta iken artık birden farklı sistemler dahilinde kullanılmak üzere tasarlanmaya başladı – tablet, bilgisayar, akıllı telefon ve televizyon gibi. Günümüzde akıllı teknolojiler ile birlikte bu sistemler daha da genişleyerek gündelik hayatta kullanılan ürünlerin da dahil olduğu bir ekosistem haline geldi. Bu ekosistem dahilindeki ürünlerin etkileşimi ile kullanıcı deneyimi bambaşka bir boyuta taşınmakta iken ürün ve etkileşimin artması kullanıcının hayatını daha karmaşık hale getirebiliyor. Artık evlerde kullanılan birçok fiziksel ürün mobil aplikasyonları ile kullanıcılara daha fazla işlev sunabilmektedir. Bu fonksiyonlar ürüne ve ürünün bağlantı seviyesine göre değişebilir. Dijital ürün (mobil aplikasyon) ve fiziksel ürün (arayüzü) arasında veri ve fonksiyonların dağılımı üç Şekilde farklılaşmaktadır. Aynı bilgi ve fonksiyonlar sistemdeki tüm cihazlarda bulunabilir (redundant), sistemdeki farklı her bir cihaz kullanıcıya farklı işlev sunabilir (exclusive), ve sistemdeki cihazlara veri ve fonksiyonları paylaşımlı olarak sunabilir (complementary). Nesnelerin interneti ile fiziksel ve dijital ürünlerin bir arada oluşturduğu ekosistem dahilinde, daha çok ürünlerin birbirlerini tamamlayarak kullanıcı faydasını artırdığı örnekler görülmektedir. Bunun yansıra akıllı ürünler dijital aplikasyonları ile fiziksel ürünleri kişiselleştirme, yönlendirme/bilgi ve otomasyon/uzaktan kontrol ile besler. Ürünler bağlantılı teknolojiler sayesinde çoklu ürün ekosistemleri haline dönürken kullanıcı – ürün ekosistemi etkileşiminin yapısı da değişir ve kullanıcı deneyimini bu çoklu- kompleks yapı altında yeniden değerlendirmek gerekir. Çoklu ürün ekosistemleri tasarımında farklı cihaz ve platformlardan erişebilirken bu deneyimin kesintisiz ve tutarlı olması esas olmalıdır. Bu sebeple çok ürün ekosistemelerin tasarımında çeşitli zorluklar bulunsa da kompozisyon, süreklilik ve tutarlılık özelliklerine mutlaka dikkat edilmelidir. Tutarlı ve bütünsel bir deneyim için çoklu cihazların kullanılabilirlik metrikleri de kulanılabirlik öznitelikleri ( aktarılabilirlik ve kullanıcı algısı) ve kullanılabilirlik özellikleri (etki, verimlilik, memnuniyet, çekicilik) altında toplanır. Bu çalışmada fiziksel ve dijital ürünlerin oluşturduğu çoklu ürün ekosistemlerinde, bir ürünün birden fazla arayüz ile kullanımınındaki kullanıcı deneyimi incelemek amaçlanmıştır. Gündelik hayatta kullanım sıklığı yüksek ve artık bağlantı teknolojileri ile akıllı versiyonlarının kullanımı artan banyo baskülü kategorisi ürünlerinden, Bluetooth bağlantılı banyo basküllerinde kullanıcıların ürün ve aplikasyon sistemi ile deneyimleri incelenmiştir. Literatür araştırması doğrultusunda bir kullanıcı deneyimi araştırması düzenlenmiştir. Ürünün hedef kitlesine uygun katılımcılar ile bir saha çalışması yürütülmüştür. Ürün kullanım senaryosu dahilinde saha-kullanılabilirlik testi ve derinlemesine görüşmelere dayanarak kullanıcı ve ürün ekosistemi arasındaki etkileşimi ve kullanıcı deneyimi incelenmiştir. Kullanılabilirlik testi içerisinde kullanıcı deneyimi soru seti ve kullanılabilirlik anketlerine başvurulmuştur. Araştırma ve analiz için kullanılan yöntem ve teknikler ilgili bölümlerde açıklanmış olup elde edilen bulgular ilgili başlıklar altında sunulmuştur. Çalışmanın sonucunda ise bir çoklu ürün ekositemi örneği olarak ele alınan Bluetooth bağlantılı basküllerde kullanıcı deneyimi araştırma sonuçları kullanıcı ile ilişkili, içeriksel ve durumsal temalar altında ayrı ayrı ele alınmıştır

While digital products are used to be applied through a product, they are designed to use in a diverse product system presently, such as a computer, tablet smartphone or TV. Moreover, while these systems are spreading with the Internet of Things (IoT), they become an ecosystem including daily life products. User-products interaction through an ecosystem moves user experience to a unique level; however, increasing the interaction and elements were raised the complexity level also. Most of the physical devices used in daily life can offer diversified functions with their mobile applications. Moreover, user interfaces appear in different forms with the prevalence of smart and connected products. For example, the lighting of the living room can be adjusted a mobile application from the smartphone or just voice command to a smart home assistant rather than the control switch on the room with the new technologies. In this example, there are several interfaces for one task; manual switch of the product, digital touch-screen interface for mobile application and voice command. From the past to the present, user-product communication has evolved by approaching the natural human communication style; gives different feedbacks such as text, light, sound. By adding a new mobile application interface to the existing user-product relationship, the need and behaviour of the user change in a more complex ecosystem with the addition of smartphones. User experience focuses on the understanding of user needs and wants in-depth. While increasing complications of the technology, more emphasis, and interest should be given user experience; moreover, to present complex technologies as efficient, easy to use and engaging UX metrics will be a more significant part of the development process. Basically, measurable elements of user experience consist of appeal, usability, and usefulness. Moreover, useful, usable, desirable, findable, accessible, credible, valuable elements included in the detailed concepts. As an important parameter of user experience, usability refers to achieve specified goals with effectiveness, efficiency, and satisfaction in a specified context of use. Information is accessible from an increasing number of platforms by people while the products are getting more complex. To deliver a seamless experience in the new growing complex systems, the user experience of the whole ecosystem should be considered. In the multi-device ecosystems, distribution of data and functions between digital (mobile app) and the physical product (interface) differs in three ways: the same information and functions can be achieved by all devices in the system (redundant), each device can offer different function and content (exclusive) or data and functions of the system are provided by devices (complementary) as shared. With smart technology, physical objects are supporting by web-based devices to increase the functions and benefits of the product. Furthermore, connected products provide personalization, guidance, and automation through their applications. The multi-device system switches our understanding of usability with the transition between devices, the ecosystem should be inter-usable also Interusability term is mean that the usability and user experience across the different user interfaces of a smart product ecosystem or overall usability of the system in this study. In addition to the use of individual devices, total system experience that offered together must be holistic and usable. While products turn into multiple device ecosystems thanks to connected technologies, the structure of the user-product ecosystem interaction changes and the user experience needs to be reevaluated under this multi-complex structure. While designing multiple product ecosystems within different devices and platforms, it should be essential that this experience is seamless and consistent. Although there are various difficulties in designing multi-product ecosystems, composition, continuity, and consistency are the main characteristics of interusability. Composition determines, the relating of each device in the system considering the distribution of functions, role allocations or modularity. Continuity provides transitions between platforms both synchronization of data and content and also task migrating of users across platforms. Consistency keeps the system coherence through perceptual (look and feel), semantic (symbol and terminology) and syntactic (interaction logic) consistency. For a consistent and holistic experience, multiple devices' usability metrics are also gathered under usability attributes (transferability and user perception) and usability features (impact, efficiency, satisfaction, attractiveness). UX emerges from the interaction of user and system within the use of context. Therefore audience of the product with all needs, behaviors, motivations; content of system with its functionality, aesthetics, responsiveness, and interaction context including time, location, culture, atmosphere, other people creates the concept of user experience. There are several examples of multi-device ecosystems which are belonged to different product categories such as action cameras, smart toothbrushes, connected food processors, robotic vacuum cleaners or smart scales. Each example can be analyzed to understand the functions of the product delivered by both the product itself and the mobile app and the system comes from this improvement. Physical products have already owned functionality can operate manually, connectivity provides secondary function as to improve products and finally, connected system should offer a new system benefit to the customer. This study aims to examine to reveal the changes in user experience from a single product to a connected- multiple device ecosystem with a Bluetooth connected bath scale example. An exploratory field study is organized according to the literature research with the target audience of the product to analyze the user experience of a multi-device ecosystem user experience. Digital bath scales are simple products to follow weight and new type Bluetooth connected versions provide more analysis and increase the interaction with users. 3 model Bluetooth connected bath scale examined in the field studies by conducting an interview and a user test study with 16 participants. Each participant is visited their home to understand the potential usage in their natural environment. In the user test section, it is applied to SUS (System Usability Scale) and UEQ (User Experience Questionnaire) surveys to evaluate the satisfaction and experience of the users. Thanks to several methods both qualitative and quantitative data and findings are provided. Surveys are analyzed with quantitative methods while observation and records were analyzed with the content analysis method. The methods and techniques used for research and analysis are described in the relevant sections and the findings obtained are presented under the related headings. As a result of the study, the user experience research results in Bluetooth related scales, which are considered as an example of a multi-product ecosystem, are discussed separately under user-related, content-related and contextual themes. This study aims to examine to reveal the changes in user experience from a single product to a connected- multiple device ecosystem with a Bluetooth connected bath scale example. An exploratory field study is organized according to the literature research with the target audience of the product to analyze the user experience of a multi-device ecosystem user experience. Digital bath scales are simple products to follow weight and new type Bluetooth connected versions provide more analysis and increase the interaction with users.
User experience in multi-device ecosystems: An evaluation on connected smart scales
Keywords: Industrial Design; Endüstri Ürünleri Tasarımı